Climate change in developing countries : results from the Netherlands climate change studies assistance programme - Drunen, M. A. van; Lasage, R.; Dorland, C. (CABI, 2006)
This book provides a comprehensive information source on The Netherlands Climatic Change Studies Assistance Programme (NCCSAP) and describes the achievements and experiences in the countries involved, i.e., Bolivia, Colombia, Ecuador, Egypt, Ghana, Kazakhstan, Mali, Mongolia, Senegal, Suriname, Vietnam, Yemen and Zimbabwe. The NCCSAP was launched in 1996 and aims to help developing countries to prepare their National Communications and to undertake capacity building, education and training activities. This book also aims to provide valuable input to the Intergovernmental Panel on Climatic Change Fourth Assessment Report. Four sections are included in the book, viz., introduction and methodology; country experiences and highlights; cross-country syntheses; and evaluation, lessons learned and outlook. The first section provides a general introduction to the NCCSAP and presents summaries of the methodologies used in the studies. Section 2 is the core of the book wherein representatives of the countries have summarized one of their studies and reflected on the strengths and weaknesses of the approach they adopted. The third section presents a cross-country synthesis for each of the sectors assessed in the countries. It also provides a cross-country analysis of the National Communications. The last section evaluates the activities in the programme in terms of content and process. Topics addressed include capacity building in the participating countries, coordination and programme management, scientific quality of studies, policy relevance of activities, contribution to climate policy development, contribution to awareness raising, donor activities and policy, etc. Experiences and lessons learned are identified and discussed. Furthermore, recommendations for future activities are discussed.